Doubling of muscle carnosine concentration does not improve laboratory 1-hr cycling time-trial performance - Chung, W.; Baguet, A.; Bex, T.; Bishop, D. J.; Derave, W. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Muscle carnosine loading through chronic oral beta-alanine supplementation has been shown to be effective for short-duration, high-intensity exercise. This randomized, placebo-controlled study explored whether the ergogenic effect of beta-alanine supplementation is also present for longer duration exercise. Subjects (27 well-trained cyclists/triathletes) were supplemented with either beta-alanine or placebo (6.4 g/day) for 6 weeks. Time to completion and physiological variables for a 1-hr cycling time-trial were compared between pre- and postsupplementation. Muscle carnosine concentration was also assessed via proton magnetic resonance spectroscopy before and after supplementation. Following beta-alanine supplementation, muscle carnosine concentration was increased by 143 ± 151% (mean ± SD; p < .001) in the gastrocnemius and 161 ± 56% (p < .001) in the soleus. Postsupplementation time trial performance was significantly slower in the placebo group (60.6 ± 4.4-63.0 ± 5.4 min; p < .01) and trended toward a slower performance following beta-alanine supplementation (59.8 ± 2.8-61.7 ± 3.0 min; p = .069). We found an increase in lactate/proton concentration ratio following beta-alanine supplementation during the time-trial (209.0 ± 44.0 (beta-alanine) vs. 161.9 ± 54.4 (placebo); p < .05), indicating that a similar lactate concentration was accompanied by a lower degree of systemic acidosis, even though this acidosis was quite moderate (pH ranging from 7.30 to 7.40). In conclusion, chronic beta-alanine supplementation in well-trained cyclists had a very pronounced effect on muscle carnosine concentration and a moderate attenuating effect on the acidosis associated with lactate accumulation, yet without affecting 1-h time-trial performance under laboratory conditions.